Detection of Virulence of Staphylococcus Aureus Isolated from Wounds - Esra F. Al-Azawi, Maryam O. Abd Alaa, Hanan Raheem Hassooni, Ali Shakir Al Ezee (Revista Electronica de Veterinaria, 2022)
The virulence factors are the degree of pathogenicity of the bacteria to the organism, which means the ability of the agent to cause disease. The virulence factors give specific characteristics of the pathogen that enable it to confront the natural defenses of the host and thus cause disease. The most important of these factors are bacterial toxins, antibiotic resistance, and the production of various enzymes, all of which help the pathogen to adapt in different environments. The virulence factor tests showed that all the (50) isolates produced biofilm and hemolysin enzyme type beta, and that all the (50) MRSA isolates were stained by Gram stain with blue color. The results showed that 47 (90%) of the isolates were urease producers, while 32 (64%) of them were protease producers, 15 (30%) isolates were lipase producers, 12 (24%) isolates were bacteriocin producers and 39 (78%) isolates were stapylokinase producers.